A normative analysis on the Gabaldon and Marcos-type design of public elementary school buildings in Davao City - Cortel, Jessa A. (2011)
In order to facilitate the delivery of good education to learners, schools need to be conducive to learning because a high quality education might not be as accessible in an unfavorable environment, such as a poorly maintained buildings. In a global context, school building design changes a new method of construction and technologies are introduced. Conversely in the Philippines, not all of these designs were able to compliment issues on building functionality, space allocation, safety and security, and ventilation, lighting, and acoustics. The study tried to analyze the impacts of the school environment to the user/occupants of the school facility, specifically the teachers and the students. It is critically important that the design, planning and construction of any school building be based on the understanding that the physical facility influences the learning climate. In addition, being confronted with a growing need for educational buildings and a significant lack of space and funds, an inquiry into the building needs at a certain level of education is needed. The aims of the inquiry are to examine the degree to which existing buildings meet present educational needs; to recognize the needs that are not met; and to develop a needs-driven design for public elementary students and teachers. Gabaldon and Marcos-type buildings along with the other school buildings types are seen to be in need of updating because of its present condition caused by its long life span. As obvious candidates for a normative case study, they aim to study is to compare these school buildings types, developing a new version of the existing buildings. Developing might also mean improving the present condition and the most functional components of the building. The variances of each school building can be used to predict future developments and improvements. The study of Gabaldon and other type of school buildings proves to be important and essential since it will start a new search for a improved learning space for the students. The Gabaldon Schoolhouse, which for the first time has set standards to regulate the quality of the Philippine learning improvement, has proven to be the best learning environment for Filipino students.